Investigation of TiO2–SiO2–CaO–CaF2 based electrode coatings on weld metal chemistry and mechanical behaviour of bimetallic welds. (August 2016) - Bhandari, Deepak; Chhibber, Rahul; Arora, Navneet; Mehta, Rajeev
Abstract: The use of nickel base alloy as filler metal is no longer considered as the final solution for unexpected failures due to incidences of hot cracking of bimetallic welds under cyclically shifted temperature environment. The present paper is a novel attempt to study the development of austenitic stainless steel filler material for bimetallic weld joint. The present work aims at the design and development of shielded metal arc welding (SMAW) electrode coatings using extreme vertices design methodology to study the effect of electrode coating ingredients on the mechanical properties such as tensile strength, percentage elongation, impact toughness, micro-hardness of the weld metal. The work also attempts to study the weld metal chemistry along with the control of ferrite number and microstructural evolution to prevent hot cracking in stainless steel welds with variation in coating ingredients. It has been found from the study that the addition of SiO2 content in the coating tends to increase the weld metal silicon content whereas the effect of CaO content is to decrease it. The ultimate tensile strength of welds is increased with the TiO2, SiO2 and CaF2 content in the electrode coating while higher SiO2 content shows decreasing effect on impact toughness and microhardness values of the weld. The microstructures of welds comprise of austenite with varying amount of delta ferrite and inclusions which are further responsible for varying mechanical properties in welds.